Influence of salinity stress on the height and productivity features of durum wheat samples in different phases of vegetation - A. Z. Sikhmuradov; A. M. Magomedov (Юг России: экология, развитие)
Influence of salinity stress on the morphological features of durum wheat in different phases of vegetation is studied in the work. It is revealed that in earlier phases the samples have weak stability, but further salt-stability increases.